Research on optical measurement for additive manufacturing surfaces - Cheng, Fang (2019)
Surfaces made by Additive Manufacturing (AM) processes normally show higher roughness and more complicated microstructures than conventional machined surfaces. In this study, AM surface roughness measurements using both tactile and optical techniques are analyzed, theoretically and experimentally. Analytical results showed both techniques have comparable performance when measuring AM samples with good surface integrity. For surfaces with steep features, coherence scanning interferometry showed more reliable performance especially when peak-to-valley value was required. In addition of the benchmarking study, development of a low-cost measurement system, using laser confocal technology, is also presented in this paper. By comparing the measurement results with those from a coherent scanning interferometer, accuracy levels of the proposed system can be evaluated. It was concluded that with comparable accuracy, the proposed low-cost optical system was able to achieve much faster measurements, which would make it possible for in-situ surface quality checking.